DESIGNING AND DEVELOPING APPROPRIATE EFL LEARNING MATERIALS REFLECTING NEW CONTEXTS AND GOALS - Y.M. Harsono (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
It is obvious that learning materials/ teaching materials/ instructional materials are one of the most crucial components for a teacher, including an English teacher, no matter where he/she teaches. “TESOL survey finds teachers spend 7 hours per week searching for instructional materials/resources and another 5 hours per week creating their own instructional materials” (Goldberg, 2017). Several similar topics about materials development have been published elsewhere in different seminar events, textbooks, and journals. They have discussed various literature about materials development such as principles and procedure of materials development (Tomlinson, n.d), guidelines for designing effective English languge teaching materials and factors to consider when designing materials (Howard and Major, n.d), language learning materials development (BİLOKCUOĞLU, 2015), developing learning materials for specific purposes (Harsono, 2007) and some others. However, none of them discussed specificly about developing appropriate EFL learning materials reflecting new contexts and goals. This paper, therefore, will review related literature around materials development, from theories – principles and procedure - to its practice from evaluating, adapting, supplementing and creating own materials, which can match with the new contexts and goals already set before.